2021
DOI: 10.1038/s41420-021-00752-1
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic signaling facilitates progression of neuroendocrine prostate cancer

Abstract: The progression of prostate cancer (PC) into neuroendocrine prostate cancer (NEPC) is a major challenge in treating PC. In NEPC, the PC cells undergo neuroendocrine differentiation (NED); however, the exact molecular mechanism that triggers NED is unknown. Peripheral nerves are recently shown to promote PC. However, their contribution to NEPC was not studied well. In this study, we explored whether sympathetic neurosignaling contributes to NED. We found that human prostate tumors from patients that later devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“… 34 The β 2 -AR has been identified as the key adrenergic receptor over β 1 -AR, promoting catecholamine-induced tumorigenesis. 35 In addition, an increasing amount of preclinical evidence supports that perioperative use of nsBBs has a beneficial effect on oncological outcome. 6 , 7 , 8 This finding could explain why an association with prostate cancer progression was only observed for nsBBs, which act on both β 1 - and β 2 -ARs, and not for sBBs, which target mainly β 1 -AR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 34 The β 2 -AR has been identified as the key adrenergic receptor over β 1 -AR, promoting catecholamine-induced tumorigenesis. 35 In addition, an increasing amount of preclinical evidence supports that perioperative use of nsBBs has a beneficial effect on oncological outcome. 6 , 7 , 8 This finding could explain why an association with prostate cancer progression was only observed for nsBBs, which act on both β 1 - and β 2 -ARs, and not for sBBs, which target mainly β 1 -AR.…”
Section: Discussionmentioning
confidence: 98%
“…34 The β 2 -AR has been identified as the key adrenergic receptor over β 1 -AR, promoting catecholamine-induced tumorigenesis. 35 In addition, an increasing amount of preclinical evidence supports that perioperative use of nsBBs has a beneficial effect on oncological [6][7][8] This finding could explain why an association with prostate cancer progression was only observed for nsBBs, which act on both β 1 -and β 2 -ARs, and not for sBBs, which target mainly β 1 -AR. Indeed, randomized clinical trials have been performed assessing perioperative use of nsBBs alone, in breast and ovarian cancer, and in combination with cyclooxygenase 2 inhibition in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study reported that patients who subsequently developed metastatic CRPC had elevated adrenergic nerve fiber innervation in the primary prostate tumors. High levels of the neurotransmitter norepinephrine, which is produced by sympathetic nerves, was shown to induce NE-like alterations in PC cells, and these effects were effectively inhibited by b 2 -adrenenergic receptor blocker propranolol (159).…”
Section: Role Of Nerves In the Development Of Prostate Cancermentioning
confidence: 99%
“…The authors showed that sympathetic axons were present within the tumor microenvironment and interacted with neoplastic cells [ 2 ]. They found the increased innervation in half of the examined tumors, interpreting that as the evidence of active axonogenesis.…”
mentioning
confidence: 99%
“…In this study, propranolol led to the inhibition of the morphological features of neuroendocrine differentiation, and inhibited the progression of PCa. Moreover, in the orthotopic tumor model, treatment with propranolol and castration significantly reduced tumor growth compared to castration alone or the control group [ 2 ]. Propranolol also affects cellular proliferation, apoptosis, inhibits angiogenesis, and regulates the immune system.…”
mentioning
confidence: 99%